Impact of Gujarat's Krishi Mahotsava (Agrarian Festival) campaigns: results of a perception survey of 1445 farmers from 25 districts - Shah, Tushaar; Pattnaik, I.; Bhatt, S.; Kopa, G.G.; Shah, A. (2013)
Since 2005, Government of Gujarat has been organising an annual, month-long, pre-monsoon Krishi Mahotsava (Agrarian Festival) campaign to expose farmer to new farming technologies and market opportunities, enhance their interaction with scientists and input suppliers, and improve their access to various government schemes. Krishi Mahotsava entails mobilisation of government machinery on a massive scale. But does it reach out to the farmer? This paper presents the results of a sample survey of 1445 farmers from across Gujarat to understand their perceptions about the Krishi Mahotsava campaign, its impact on them and their suggestions about how to enhance its usefulness to them.